Reaksi Pasar terhadap Pembentukan Super Holding Danantara di Indonesia: Danantara di Indonesia (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study is motivated by the formation of the Danantara Super Holding, which has the potential to influence the reaction of the Indonesian capital market. This study aims to analyze the differences in abnormal returns and trading volume activity before and after the formation of the Danantara Super Holding. This study uses a quantitative approach with an event study method on 15 state-owned enterprises (SOEs) with an observation period of 15 days before and 15 days after the event. Data were collect using the documentation method through secondary data obtained from the Indonesian Stock Exchange (IDX). The data analysis technique uses the Paired Sample t-Test with SPSS 25 software. The results show that there is no significant difference in abnormal returns or trading volume activity before and after the formation of the Danantara Super Holding. This indicates that the capital market has not yet reacted significantly to information related to the formation of the Danantara Super Holding. This condition indicates that information regarding the formation of the Danantara Super Holding has not been fully perceived as having strong information content by investors